1992
DOI: 10.1007/bf00184347
|View full text |Cite
|
Sign up to set email alerts
|

Licht- und rasterelektronenmikroskopische untersuchungen zur pathogenese des sinus pilonidalis und der analristel

Abstract: From various theories about the development of the pilonidal sinus Stelzner's opinion as to an acquired disease is generally accepted. Our scanning electron microscopic investigations strengthen this theory that hair splits and drills into the skin. Hooks keep it from retracting. Needlelike sharp ends may contribute to the hair piercing the skin. The anal fistula differs from the pilonidal sinus concerning morphology and pathogenesis. Surgical treatment must consider the localisation of the proctodeal gland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 9 publications
1
1
0
1
Order By: Relevance
“…The study by Dahl and Henrichs has focused on the morphological aspects of the hair commonly found inside pilonidal sinus [12]. Although their scanning electron microscopic pictures of hair ends are similar to our pictures, they conclude hair ends were broken.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The study by Dahl and Henrichs has focused on the morphological aspects of the hair commonly found inside pilonidal sinus [12]. Although their scanning electron microscopic pictures of hair ends are similar to our pictures, they conclude hair ends were broken.…”
Section: Discussionsupporting
confidence: 54%
“…Karydakis hypothesized multiple hair‐related factors promoting PSD [9–11], but only one study has evaluated the microscopic morphology of hair found inside the sinus [12]. It may be easy to differentiate between hair of Asian, African and Caucasian individuals [13], but not if the individual is a genetic blend [14].…”
Section: Introductionmentioning
confidence: 99%
“…Dahl et al confirmed the hook morphology and showed that the proposed sharp tips contribute to hair puncturing the skin, meaning hook formation prevents retraction. Gosselink et al On the other hand, he states that the direction of the hair scales probably encourages the hair to be driven deeper into the tissue (15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…Der PS wird heute überwiegend als eine erworbene Erkrankung angesehen, bei der Haare eine entscheidende Rolle in der Pathogenese spielen [33 -35]. Durch Reibebewegungen der Haut durchdringen Haare die Epidermis und lösen eine Fremdkörperreaktion aus, was zu einer chronischen Entzündung mit Bildung von Granulationsgewebe und Fisteln führen kann [36,37]. Übergewicht, Nikotinkonsum, mangelnde perianale Hygiene, Hyperhidrose und starke Behaarung zählen zu den wichtigsten Risikofaktoren [34, 38 -40].…”
Section: Pilonidalsinusunclassified